Ulnar collateral ligament reconstruction does not decrease spin rate or performance in Major League pitchers - Cinque, M. E.; LaPrade, C. M.; Abrams, G. D.; Sherman, S. L.; Safran, M. R.; Freehill, M. T. (The American Journal of Sports Medicine, 2022)
Background: Ulnar collateral ligament reconstruction (UCLR) is commonly performed in Major League Baseball (MLB) pitchers, with variable reported effects on velocity and traditional rate statistics. Currently, no studies have evaluated spin rate in the context of return to play (RTP) after injury. Greater spin rate has become increasingly sought after in the baseball community, as it is believed to be a vital aspect of pitch effectiveness.